Fuzzy process capability indices for simple linear profile. Issue 12 (9th September 2020) - Abbasi Ganji, Zainab; Sadeghpour Gildeh, Bahram
Abstract : Process capability indices are numerical tools that quantify how well a process can meet customer requirements, specifications or engineering tolerances. Fuzzy logic is incorporated to deal imprecise, incomplete data along with uncertainty. This paper develops two fuzzy methods for measuring the process capability in simple linear profiles for the circumstances in which lower and upper specification limits are imprecise. To guide practitioners, numerical example is provided.